Somatic Mutation of FAT Family Genes Implicated Superior Prognosis in Patients With Stomach Adenocarcinoma - Wang, Qingjun; Cui, Liang; Li, Pansong; Wang, Yuanyuan (Frontiers in Medicine, 2022)
FAT family genes encode protocadherin, which regulates tumor cell proliferation and migration. Although transcriptional levels of FAT family members had been reported in multiple malignant tumors, the association between mutation and prognosis of the FAT family in stomach adenocarcinoma (STAD) has not been investigated. Herein, we performed a multi-omics integrative bioinformatics analysis using genomic and mRNA expression data to explore the role of gene mutations across the FAT family on clinical outcomes of STAD. The results showed that FAT mutations occurred in 174 of 435 (40%) of the samples. Patients with FAT mutations possessed significantly better progression-free survival (P=0.019) and overall survival (P=0.034) than those with non-FAT mutations, and FAT mutations exhibited significantly higher tumor mutational burden (TMB) and microsatellite instability. Notably, FAT mutations had a greater effect on somatic single nucleotide variation than copy number variation, and resulted in more abundant DNA damage repair (DDR) mutations. Further investigation demonstrated that FAT mutations contributed to an inflammatory tumor microenvironment (TME), as indicated by significantly increased numbers of activated CD4 and CD8 T cell, and significantly decreased numbers of Mast cell, Plasmacytoid dendritic cell, and Type 2 T helper cell, and high expression of immune-promoting genes. Moreover, biological process antigen processing and presentation, DNA replication, and DDR related pathways were significantly upregulated in patients with FAT mutations. Collectively, FAT mutations significantly improved survival of patients with STAD by enhancing tumor immunogenicity (including TMB, DDR mutations) and an inflamed TME, indicating that FAT family might be a potential prognostic and therapeutic biomarker for STAD.